Econometric analysis of supply chain disruptions: financial performance in the European automotive sector - Viviane Naimy; Tatiana Abou Chedid; Nicolas Bitar (Electronic Research Archive)
We investigated the relationship between supply chain disruptions (SCD) and the financial performance (FP) of European automotive companies across emerging and developed nations. Addressing gaps in the literature, it offers a comprehensive, industry-specific analysis using panel data from 73 automotive firms across 21 European countries from 2013 to 2022. We examined the impact of SCD on return on assets (ROA), return on equity (ROE), and stock returns (SR), while controlling for factors such as age, leverage, size, economic growth, inflation, and unemployment. Our findings revealed that disruptions related to industrial materials and iron prices (IRAW) positively influence stock market performance, with a 99.5% increase in SR per 1% rise in IRAW, suggesting increased demand. Conversely, precious metal prices negatively affected all financial metrics, reducing ROE by 17.3% and SR by 55.5% per 1% increase. Heightened shipping costs showed varied impacts on ROA and ROE but contributed to a 12.9% average increase in SR, indicating effective cost transfer to consumers. The pandemic years significantly decreased ROA, ROE, and SR, highlighting challenges faced by the automotive sector. Rising oil prices showed no significant association, underscoring the importance of hedging strategies. The control variable outcomes emphasize the need for detailed evaluation in assessing financial performance. This study's contribution lies in its detailed analysis of specific disruptions within the automotive industry and their distinct impacts on financial performance metrics, providing a nuanced understanding that addresses significant gaps in the existing literature.